PEMBENTUKAN MODEL PERLINDUNGAN ANAK BURUH MIGRAN DI KABUPATEN BANYUMAS - Riris Ardhanariswari; Waluyo Handoko; Sofa Marwah (Jurnal Dinamika Hukum, 2012)
This paper discusses about the model of protection children of migrant workers that most appropriate and can be used as a reference for the model of child protection that more comprehensive. The approach used in this study is a qualitative action research approach. The selected research location include two villages that representing the rural and semi-urban areas of two districts which they are the basis of migrant workers, such as Kedondong Village District of Sokaraja (semi-urban) and Dawuhan Kulon Village District of Kedungbanteng (rural). Data were selected by using purposive sampling method. Base on research, Model of child protection of migrant workers can be done by more empowering form of social workers in the district by establishing a new institution, the Board for Child Protection of Migrant Workers (BCPMW) at sub-district and district levels. Membership BCPMW at district level consisting of components Dinsosnakertrans, prospective migrant workers migrant workers, recruitment agency, social worker and observer problems of migrant workers. In carrying out its functions and duties, BCPMW have partnered with Dinsosnakertrans and BapermasPPKB. Keywords: children of migrant workers, child protection model of migrant workers